Adaptation and Evaluation of Military Resilience Skills Training for Pediatric Residents. (16th November 2017) - Bursch, Brenda; Lloyd, Jessica; Mogil, Catherine; Wijesekera, Kanchana; Miotto, Karen; Wu, Michelle; Wilkinson, Rebecca; Klomhaus, Alexandra; Iverson, Arija; Lester, Patricia
Background: An evidence-based trauma-informed resilience skills training program developed for deployed military personnel was adapted and pilot-tested with pediatric residents. We anticipated high satisfaction ratings and changes in knowledge, beliefs, and self-efficacy related to coping with stress and trauma. Methods: The intervention included 6 skill-based modules covering emotion regulation, communication with angry patients and parents, reflective narrative, inspirational goal setting, problem-solving, and developing a self-care toolbox. An optional survey was administered before and after the training. Results: After training, 76% rated resilience skills as important, 60% were satisfied, and 82% indicated the training changed how they will respond to patient-related grief and trauma. They became more likely to believe attendings are affected by patient deaths and to know what helps them cope when they disagree with the medical decision making of others, more skilled in recognizing signs of stress and trauma, and more knowledgeable about evidence-based interventions.